The Political Marketing: Winning Strategies in Presidential Election Contestation - Mujiono, Berkah Cahyo; Atmoko, Waluyo Budi; Yulandari, Ariefah (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Voting behavior is an important factor that plays a major role in determining the victory of a political candidate. This research aims to examine voting behavior variables. A person's voting behavior is influenced by voter confidence and candidate popularity. This research was conducted through a questionnaire distributed to respondents who met the requirements to vote (age> 17). The sampling technique used was purposive sampling of 200 respondents. The hypothesis testing tool used in this research is logistic regression analysis. The research results show that voter trust and candidate popularity have a positive effect on voting behavior. The candidate popularity variable partially mediates the relationship between voter trust and voting behavior. Candidate popularity partially moderates the relationship between voter trust and voting behavior. These results suggest that candidates competing to win the election should maintain voter confidence and increase the candidate's popularity in society.